Association between ε2/3/4, Promoter Polymorphism (−491A/T, −427T/C, and −219T/G) at the Apolipoprotein E Gene, and Mental Retardation in Children from an Iodine Deficiency Area, China. (25th March 2014) - Li, Jun; Zhang, Fuchang; Wang, Yunliang; Wang, Yan; Qin, Wei; Xing, Qinghe; Qian, Xueqing; Guo, Tingwei; Gao, Xiaocai; He, Lin; Gao, Jianjun
Abstract : Background. Several common single-nucleotide polymorphisms (SNPs) at apolipoprotein E (ApoE) have been linked with late onset sporadic Alzheimer's disease and declining normative cognitive ability in elder people, but we are unclear about their relationship with cognition in children. Results. We studied - 491 A / T, - 427 T / C, and - 219 G / T promoter polymorphisms and ε 2 / ε 3 / ε 4 at ApoE among children with mental retardation (MR, n = 130 ), borderline MR (n = 124 ), and controls (n = 334 ) from an iodine deficiency area in China. The allelic and genotypic distribution of individual locus did not significantly differ among three groups with Mantel-Haenszel χ 2 test (P > 0.05 ). However, frequencies of haplotype of - 491 A /- 427 T /- 219 T /ε 4 were distributed as MR > borderline MR > controls (P uncorrected = 0.004), indicating that the presence of this haplotype may increase the risk of disease. Conclusions. In this large population-based study in children, we did not find any significant association between single locus of the four common ApoE polymorphisms (- 491 A / T, - 427 T / C, - 219 T / G, and ε 2 / 3 / 4 ) and MR or borderline MR. However, we found that the presence of ATTε 4 haplotype was associated with an increased risk of MR and borderline MR. Our present work may help enlarge our knowledge of the cognitive role of ApoE across the lifespan and the mechanisms of human cognition.